Each niche has an actor: multiple stem cell niches in the preterm kidney. Issue 1 (December 2015) - Fanni, D.; Sanna, A.; Gerosa, C.; Puddu, M.; Faa, G.; Fanos, V.
Abstract The preterm kidney cannot be simply considered as a kidney small in size: as compared to the adult kidney, the developing organ of the preterm infant is characterized by marked differences regarding the architecture and cell components. At macroscopy, fine linear demarcations indenting the renal surface characterize the fetal and preterm kidney. At microscopy, multiple major architectural changes differentiate the developing kidney from the adult one: a large capsule with a high cellularity; the branching ureteric bud, extending from the hilum towards the renal capsule; striking morphological differences among superficial (just born) and deep (more mature) glomeruli; persistence of remnants of the metanephric mesenchyme in the hylum; incomplete differentiation of developing proximal and distal tubules. At cellular level, kidneys of preterm infants are characterized by huge amounts of stem/precursor cells showing different degrees of differentiation, admixed with mature cell types. The most striking difference between the preterm and adult kidney is represented by the abundance of stem/progenitor cells in the former. Multiple stem cell niches may be identified in the preterm kidney, including the capsule, the sub-capsular nephrogenic zone, the cap mesenchyme embracing the ureteric bud tips, the cortical and medullary interstitium, and the hilar zone in proximity of the ureteric origin. The sub-capsular area represents the major stem cell niche in the prenatal kidney. It has been defined "blue strip", due to the scarcity of cytoplasm of the undifferentiated stem/progenitors, which appear as small cells arranged in a solid pattern. All these data taken together, the morphological approach to the analysis of the preterm kidney appears completely different from that typically utilized in kidney biopsies from adult subjects. Such a different structure should be taken into account when evaluating renal function in a preterm infant in clinical practice. Moreover, a better knowledge of molecular biology of the blue strip stem/progenitor cells could be at the basis of a new "endogenous" regenerative medicine, finalized to maintain and protect the nephrogenic potential of preterm infants till the 36th week of post-conceptional age, allowing them to escape oligonephronia and chronic kidney disease later in life.